Peptic ulcer hemorrhage: comparison of efficacy of two methods of endoscopic hemostasis - a prospective study - Skok, Pavel (Zdravniški vestnik, 2004)
Background. Interventional endoscopy has largely reduced mortality in patients with peptic ulcer hemorrhage. Study aims. To evaluate the efficacy and safety of endoscopic hemostasis with argon plasma coagulation and injection sclerotherapy in bleeding peptic ulcer and determine the mortality of patients in a prospective, controlled study. Patients and methods. The study includes 100 patients with peptic ulcer hemorrhage (male 63, female 37, av. age 57.1 years, SD +/- 16, span 26-80; gastric ulcer 50 patients, duodenal ulcer 50 patients) in the period between 1 Jan. 1999 and 15 May 2000 treated in our institution. The bleeding activity was determined according to Forrest classification. Fifty patients were randomized to receive argon plasma coagulation (ARCO 2000 Electro Surgery unit, group A) and in fifty patients injection sclerotherapy (sclerosing with diluted adrenalin 1:10,000 plus polidocanol 1%, group B) was performed. The groups did not differ with respect to age, sex, site, severity of bleeding, use of NSAID and additional diseases. Results. Clinically and endoscopically diagnosed reebleding occured in 7/50 patients (14%) in group A and in 9/50 patients (18%) in group B; p = 0.78. The majority of reebleding occured within 48 hours after endoscopic hemostasis, group A 4/7 (57.1%), group B 7/9 (77.7%), p = 0.74. Repeated endoscopic hemostasis did not prove successful in 8 patients (group A 3/50, 6%, group B 5/50, 10%), p = 0.71. Seven patients were treated operatively. The total mortality rate was 9% (9/100 patients, group A 4/50, 8%, group B 5/50, 10%), p > 0.05. Only one patient died due to peptic ulcer hemorrhage, other 8 patients died due to concomitant diseases. Conclusions. Argon plasma coagulation seems to be an effective and safe alternative to injection sclerotherapy and other hemostatic modalities in peptic ulcer hemorrhage.
Keywords: Argon; Coagulation; Endoskopska hemostaza; Hemostasis, endoscopic; Koagulacija; Peptic ulcer hemorrhage; Peptična razjeda, krvavitev; Sclerotherapy; Skleroterapija